Internet of things and smart warehouses as the future of logistics - Krešimir Buntak; Matija Kovačić; Maja Mutavdžija (Tehnički Glasnik, 2019)
Innovations and market changes in warehouse and logistics systems force the adaptation and transformation of the existing business model into a business model based on modern technology. With the development of the Internet, RFID (radio-frequency identification) technology and sensors, new innovations are being created that allow the improvement of the existing mode of activity. Implementation of the new technology brings along a number of challenges that organizations must find an adequate response to. However, warehouse systems are not the only affected by the new technologies. The development of technology and technological innovations enable organizations to develop sustainability. Sustainable development is imperative due to increasing awareness of the need for environmental protection. The supply chain can also be managed much more efficiently if sensors that collect information of customer habits and process performance are implemented. Given the accelerating development of Industry 4.0 and the opportunities offered by newly developed technology, this paper provides an overview of current developments in the implementation of Industry 4.0 technological innovations in logistics.